Effect of thermal treatment on the bending strength of glass ceramic/resin cement - Saavedra, Guilherme Siqueira Ferreira Anzaloni; Pedrique, Beatriz; Cavalheiro, Rodrigo Furtado; Borges, Alexandre Luiz Souto; Paes-Junior, Tarcisio José de Arruda (Brazilian Dental Science, 2013)
Objectives: To investigate the effect of the thermal treatment on the bending strength of ceramic bars (VM7) treated by the cementation protocol. Material and Methods: Forty ceramic bars (20 x 4 x 1.2 mm) were constructed and randomly distributed into 2 groups (n=20): NT - without treatment/control and T – with treatment (50°C above the glass transition temperature, for 15 min). All specimens underwent the cementation process in which one surface of the ceramic bar was etched (20 s) with 10% hydrofluoridric acid, followed by air-water jet washing (60 s), drying (30 s), silane agent application and resin cementation. After storage (distilled water/seven days at 37 ºC), the specimens were submitted to 3-point flexure test at 100% humidity/37 ºC (v=1 mm/min, load cell of 10 kgf). Results: The bending strength values and standard deviations (MPa) were: NT: 19.98 (3.17)a; T: 20.45 (4.67)a (one-way ANOVA and Tukey test, ?=0.05). Conclusions: The thermal treatment did not influence on the bending strength mean values of the ceramics studied.